Hubungan Konsumsi Sayur dan Buah dengan Frekuensi Buang Air Besar pada anak remaja di SMAN 7 Kota Bengkulu - Sirait, Ester; Krisnasarry, Arie; Yulianti, Risda (Jurnal Nutrire Diaita (Ilmu Gizi), 2024)
Vegetables and fruits are the easiest source of fiber to find and one of the functions of fiber is to nourish the gastrointestinal tract, fiber has various mechanisms in increasing stool volume, dietary fiber will bind water in the human colon, which makes the volume of stool larger and stimulates the nerves in the rectum to cause the urge to defecate. The average fiber consumption in the general population in Indonesia is 10.5 grams / day, while the ideal fiber requirement is 25-30 grams daily. This research is descriptive analytic research, using cross sectional research design. The population in this study were all students of class X and XI at SMAN 7 Bengkulu City with a sample of 94 people taken by random sampling. Data collection of vegetable and fruit consumption with semi-quantitative Form food questionnaire (FFQ) method, defecation frequency data using questionnaire and data analysis using Spearman correlation test. The average high school student consumes 309 g/day of vegetables and fruit and the average frequency of defecation of high school students is 4.5 x/week. The results of the Spearman correlation statistical test showed that there was a significant relationship between consumption of vegetables and fruit and the frequency of defecation with a value of p=0.067. There is no significant relationship between vegetable and fruit consumption and the frequency of defecation in adolescents at SMAN 7 Bengkulu City. Suggestions for future researchers can continue or develop this research and for SMAN 7 Bengkulu City it is hoped that it can continue to increase consumption of vegetables and fruit.Keyword: Consumption of Vegetables and Fruits, Frequency of Defecation21 Bibliography, 2013-2022